More NRI leaflets for extension workers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Natural Resources Institute has introduced a new series of technical leaflets for use by extension and similar workers. The first in the series How to make fish drying racks, was announced in Spore 30. Two more are now available, Use of ice by...